Role of the dorsolateral prefrontal cortex in processing temporal anomalies retained in working memory - Mirino, Pierandrea; Quaglieri, Alessandro; Scozia, Gabriele; Mercuri, Sara; Alessi, Alessandro; Guariglia, Cecilia; Giannini, Anna Maria; Doricchi, Fabrizio; Pecchinenda, Anna (Frontiers in Behavioral Neuroscience, 2024)
Time is a crucial abstract construct, allowing us to perceive the duration of events. Working memory (WM) plays an important role in manipulating and storing the different features of environmental stimuli, including temporal features. Different brain structures, including the dorsolateral prefrontal cortex, are involved in time processing. Here we investigated the functional aspects of time processing by using functional near-infrared spectroscopy (fNIRS) to assess changes in DLPFC activity. A modified version of the "Times Squares Sequences" (TSS) task was used, in which participants are required to match sequences of squares that have fixed or variable durations. Findings showed that the DLPFC activates when information necessary for later comparison needs to be maintained online, as is common in visuo-spatial WM tasks. Importantly, the DLPFC deactivates when a temporal anomaly is detected. This deactivation occurs because the temporal anomaly does not require ongoing maintenance for later comparison, thus demanding fewer cognitive resources from the DLPFC. This seemingly counterintuitive effect can be attributed to the temporal aspects being irrelevant to the primary task goals. This finding highlights the crucial role of implicit temporal interference and establishes a strong connection between timing and executive cognitive processes.